2011
DOI: 10.4103/0377-4929.81599
|View full text |Cite
|
Sign up to set email alerts
|

Strong BCL2 expression in Burkitt lymphoma is not uncommon in adults

Abstract: It was concluded that contrary to the common belief, strong BCL2 IHC expression is possible in typical BL in adults and cannot be absolutely relied upon to distinguish between BL and DLBCL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
1
4
0
2
Order By: Relevance
“…Gain of 18q21 encompassed MALT1, BCL2, and TCF4 and had corresponding upregulated mRNA and/or mutation. BCL2 protein/mRNA expression was higher in adult BL, consistent with earlier studies, 53 and co-occurred with MCL1 (1q21 gain) another antiapoptotic protein. BL cell lines were more sensitive to a pan-BCL2 inhibitor (Sabutoclax) than to agents targeting single BCL2 family members, suggesting a potential target in adult BL.…”
Section: Discussionsupporting
confidence: 91%
“…Gain of 18q21 encompassed MALT1, BCL2, and TCF4 and had corresponding upregulated mRNA and/or mutation. BCL2 protein/mRNA expression was higher in adult BL, consistent with earlier studies, 53 and co-occurred with MCL1 (1q21 gain) another antiapoptotic protein. BL cell lines were more sensitive to a pan-BCL2 inhibitor (Sabutoclax) than to agents targeting single BCL2 family members, suggesting a potential target in adult BL.…”
Section: Discussionsupporting
confidence: 91%
“…Particularly, increased expression of antiapoptotic Bcl-2 family members and/or reduced expression of specific proapoptotic members are typical features of B cell lymphomas [ 35 ]. Pervez et al [ 36 ] demonstrated strong diffuse cytoplasmic staining for Bcl-2 in specimens taken from an adult patient diagnosed with BL.…”
Section: Discussionmentioning
confidence: 99%
“…The tumors display the typical histological features of Burkitt's lymphoma and are markedly positive for EBV. Weak BCL2 expression is still compatible with the diagnosis of Burkitt's lymphoma [4]. Contrary to common belief, strong BCL2 IHC expression is possible in typical Burkitt's lymphoma in adults and cannot be absolutely relied upon to distinguish between Burkitt's lymphoma and DLBCL [5].…”
Section: Discussionmentioning
confidence: 99%